Sharia Legal Framework: A Comparative Analysis of Religious Courts in Brunei Darussalam and Indonesia - Lagus, Wegestin; Asasriwarni; Zulfan, Zulfan (Reformasi Hukum, 2024)
The application of sharia law in the religious justice system has significant variations between countries, including Brunei Darussalam and Indonesia. The main issue raised in this article is how the two Muslim-majority countries implement different legal systems, both in the legal structure, the role of religious leaders, and the scope of the application of sharia law. This article aims to analyze a comparative comparison of the legal and religious justice systems in Brunei, Darussalam, and Indonesia and their implementation practices. This study uses a qualitative and comparative descriptive approach to analyze legal regulations and their implementation in both countries. The results show that Brunei implements a dual legal system separating civil and Sharia law, emphasising stricter Sharia criminal law, including hudud and qisas. In contrast, Indonesia applies sharia law limited to family law with religious justice integrated into the national justice system. This difference is influenced by the role of the Sultan in Brunei as the leader of religion and state. At the same time, in Indonesia, there is a separation of power between the executive, legislative, and judicial. This study recommends that Brunei needs to strengthen human rights protection in the application of sharia law. At the same time, Indonesia is advised to improve coordination between religious courts and general courts for more equitable justice.